Evaluating outcomes of the child and adolescent psychiatric unit: A prospective study - Setoya, Yutaro (BioMed Central, 2011)
BACKGROUND: The aims of this prospective study are to clarify the outcomes of child psychiatric inpatient treatment and to identify factors associated with patient improvement. METHODS: The attending psychiatrist used the Children's Global Assessment Scale (CGAS) to assess youths at admission to and discharge from a child and adolescent psychiatric unit in Japan(N = 126, mean age = 12.8, SD = 1.9). Hospital records gathered sociodemographic and clinical variables. In addition, youths and their primary caregivers assessed themselves using the Youth Self Report (YSR) and the Child Behavior Checklist (CBCL), respectively. Longitudinal analyses compared each scales' baseline and discharge scores. We also examined factors associated with changes in functioning (CGAS). RESULTS: Longitudinal comparisons revealed that CGAS, CBCL and YSR scores showed improvement over time (CGAS: t = -14.40, p = 0.00; CBCL: t = 3.80, p = 0.00; YSR: t = 2.40, p = 0.02). Linear regressions determined that the factors associated with improvement in CGAS included age, lower CGAS scores at admission, frequency of group therapy and psychiatric diagnosis. CONCLUSIONS: This evaluation of children and adolescents in an inpatient unit demonstrated clinical improvement over time and identified factors associated with said improvement.